OBJEKTİF CEZALANDIRILABİLME ŞARTI VE ZAMANAŞIMI - (:unkn) unknown (My University, 2013)
Zamanaşımı, kanunda öngörülen belli sürelerin geçmesi ile devletin cezalandırma yetkisini ortadan kaldırmaktadır. Zamanaşımı, şüpheli, sanık veya hükümlü için kanun tarafından tanınmış bir haktır. Objektif cezalandırılabilme şartı içeren suçlarda, zamanaşımı suçun işlendiği günden itibaren işlemeye başlar.

By running of certain periods of time which are prescribed by law, statute of limitations remove the government s authority of penalization. Limitation is a right given by law for the suspect, accused and convicted. For crimes which have objective conditions of criminality, the limitation period shall begin on the day the crime was committed.
Objective Condition of Criminality and Limitation
Keywords: Hukuk